THE NANAI CLAN SAMAR: TSTRUCTURE OF GENE POOL BASED ON Y-CHROMOSOME MARKERS - Y. V. Bogunov; O. V. Maltseva; A. A. Bogunova; E. V. Balanovskaya; Ю. В. Богунов; О. В. Мальцева; А. А. Богунова; Е. В. Балановская (IAET SB RAS, 2016)
Members of the Nanai clan Samar reside in the Gorin area of the Khabarovsk Territory. Their gene pool was studied using the SNP markers of the Y-chromosome. The major haplogroup, occurring in more than 83 % of clansmen, is the northern Eurasian haplogroup N1c1-M178. Four other haplogroups are С*-М130, I*-M170, J2a1а-M47, and O2-P31. The most frequent haplogroup, N1c1-М178, indicates mostly Tungus origin of the Samar clan; other haplogroups detected by complete sequencing, such as the minor haplogroup C3*-M130, reveal ties with native populations of the Amur basin. Genetic distances and their multidimensional scaling demonstrate marked affinities of Samar clansmen with Yakuts, Khakas, and certain groups of Buryats, suggesting a common origin. Nanai of other regions are much further from the Samar. Показано современное расселение нанайского рода Самар (горинская группа нанайцев, Хабаровский край). Изучен генофонд популяции по SNP-маркерам Y-хромосомы. Его основу составляет североевразийская гаплогруппа N1c1-M178 (более 83 %), представлены также еще четыре: С*-М130, I*-M170, J2a1а-M47, O2-P31. Мажорная гаплогруппа N1c1-М178 маркирует преимущественное тунгусское происхождение рода, тогда как полное секвенирование Y-хромосомы образца с минорной гаплогруппой C3*-M130 выявило и связи с коренными популяциями Амура. Рассчитанные генетические расстояния и график многомерного шкалирования демонстрируют значительную генетическую близость нанайского рода Самар с якутами, хакасами и отдельными группами бурят. Это позволяет сделать вывод об их общем происхождении. Нанайцы других регионов находятся на значительном генетическом расстоянии от горинских самагиров.